Zeolite Y microspheres with perpendicular mesochannels and metal@Y heterostructures for catalytic and SERS applications. Issue 15 (14th March 2018) - Chen, Zhuwen; Chen, Chao; Zhang, Jian; Zheng, Guangchao; Wang, Yanding; Dong, Lei; Qian, Wei; Bai, Shan; Hong, Mei
Abstract : Zeolite Y microspheres with perpendicular mesochannels are prepared by using mono-alcohols as growth modifiers and carnitine for internal architecture modulation. Abstract : The control over particle shape and internal architecture offers promise to better realize catalytic activity and selectivity through structural optimization but remains a challenge for crystalline zeolite frameworks. This work describes a facile one-pot strategy to synthesize uniform zeolite Y microspheres through epitaxial hydrogen bonding and entropic hydrophobic interactions using simple mono-alcohols as zeolite growth modifiers with judicious adjustment of synthesis parameters. The internal architecture can be fine-tuned by the co-presence ofl -carnitine which creates hidden defects. Unprecedented wheel-like mesoporous channels are created within the microspheres by acid attack of the induced weak points. Moreover, the combination of zeolite Y microspheres with other materials is expected to impart additional properties due to the hybrid nature of the resulting nanocomposites and the perpendicular mesochannels for alleviated diffusion. As demonstrated, Pd 2+ -exchanged microspheres exhibit remarkably enhanced catalytic activity and recyclability for C–C coupling reactions, and metal doped Ag@Y microspheres allow for fast sensing by surface-enhanced Raman scattering (SERS), achieving orders of magnitude lower detection limit for water soluble molecules.